2019
DOI: 10.1016/j.molp.2018.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Histone H2B Monoubiquitination Fine-Tunes Abscisic Acid Signaling and Drought Response in Rice

Abstract: Histone H2B monoubiquitination (H2Bub1) plays important roles in several physiological and developmental processes, but its roles in the regulation of plant stress responses remain elusive. Here, we report that H2Bub1 is crucially involved in abscisic acid (ABA) signaling and drought response in rice. We found that rice HISTONE MONOUBIQUITINATION2 (OsHUB2), an E3 ligase for H2Bub1, interacted with OsbZIP46, a key transcription factor regulating ABA signaling and drought response in rice. Genetic analyses sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 60 publications
2
36
0
1
Order By: Relevance
“…GmUBC9 showed the highest percent identities with AtUBC1/2 ( Figure 2A; Supplementary Figure S6). AtUBC1/2 is an important enzyme that mediates histone H2B monoubiquitination, thereby broadly impacting plant growth and development, such as drought stress responses and flowering (Cao et al, 2008;Xu et al, 2009;Chen et al, 2019;Ma et al, 2019). Our study confirmed that GmUBC9 has the same function in soybeans, and they are all involved in H2B monoubiquitination.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…GmUBC9 showed the highest percent identities with AtUBC1/2 ( Figure 2A; Supplementary Figure S6). AtUBC1/2 is an important enzyme that mediates histone H2B monoubiquitination, thereby broadly impacting plant growth and development, such as drought stress responses and flowering (Cao et al, 2008;Xu et al, 2009;Chen et al, 2019;Ma et al, 2019). Our study confirmed that GmUBC9 has the same function in soybeans, and they are all involved in H2B monoubiquitination.…”
Section: Discussionsupporting
confidence: 73%
“…UBC gene family members have been documented and characterized in a range of plants (Cao et al, 2008;Xu et al, 2009;Chen et al, 2019;Ma et al, 2019). Herein, we conducted a genome-wide assessment of UBC genes in soybeans, identifying 91 such putative UBC genes in total ( Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations